Perancangan Aplikasi Peminjaman Pada PT. BANK Perkreditan Rakyat (BPR) Pijer Podi Kekelengan Medan dengan Metode Secure Election Protocol - Matondang, Zekson Arizona; Gulo, Mega Sastri Indah Lestari (MEANS (Media Informasi Analisa dan Sistem), 2020)
In the era of computerization of information that has developed rapidly there is a growing operating system including mobile phones and smartphones. Android is software for mobile devices that includes the Android operating system equipped with an Android SDK (Software Development Kit) that provides tools and supports the need for API (Application Programming Interface) needed to develop loan registration and simulation applications at PT BPR Pijer Podi Kekelengen Medan Secure Election Protocol Method. Pijer Rakyat Credit Bank Podi Kekelengen is a financial institution that functions to serve credit and savings for customers. Simulation is a calculation that gives an idea of the amount of installments in a financing. Loan registration and simulation applications can provide information to prospective customers about product.